DIAGNOSIS OF A PERSON’S STRESS RESISTANCE LEVEL - Boyanbayeva Sholpanay Bahitbayevna; Yesemuratova Ziyada Jalgasbayevna (Лучшие интеллектуальные исследования, 2024)
Abstract: this article shows that today psychologists have conducted many studies of human thinking, psychological changes in it, in which much attention is paid not only to their own psychology, but also to the problem of their health. It also describes the stressful situations that arise in a person (complex life situations that lead a person into a state of stress) and the psychological mechanisms of reactions to him. It also psychologically reveals the importance of the qualities of optimism and pessimism that are present in a person when overcoming stressful situations.